OBIEE 11g reports and dashboards - Hotka, Dan; Safari eBooks ([Place of publication not identified] : Prentice Hall, 2015)
"OBIEE 11g (Oracle Business Intelligence Enterprise Edition) Reports and Dashboards LiveLessons introduces students to the querying and analytical capabilities of Oracle Analytics using the web interface. This course is primarily for business analysts or programmers utilizing OBIEE for analysis. Students will leave the course being able to produce reports and retrieve information from the Oracle RDBMS using the OBIEE web interface. In this LiveLessons video course, Oracle Ace Director Dan Hotka covers how to create, modify, run, and refine ad hoc queries. Students will learn to view, chart, and analyze multidimensional data. They will also learn to produce individual ad hoc reports and make these reports and information easy to access (dash boards). The final lesson focuses on using BI Publisher to transform these reports into polished/formatted/quality reports in about any language or format required."--Resource description page.
Title from title screen (viewed October 26, 2015).
Presenter, Dan Hotka.
Keywords: Oracle (Computer file); Data mining; Electronic books